Clinical Features and Familial Mutations in an Autosomal-Inherited Alport Syndrome Patient With the Presentation of Nephrotic Syndrome - Wang, Dahai; Shan, Chunrong; Jing, Xinxin; Zhang, Qiuye; Chang, Hong; Lin, Yi (Frontiers in Pediatrics, 2021)
Background: The aim of this study was to report the clinical features and mutations in a patient with autosomal-inherited Alport syndrome (AS). Methods: We examined the clinical data, mutation analysis results, and family tree of a patient with autosomal-inherited AS, who had nephrotic syndrome as her first manifestation. Results: The proband was a girl of 11 months who presented with nephritic and nephrotic syndromes including gross hematuria but had a normal renal function. Her treatment course was complicated by steroid resistance and a poor response to cyclosporine A and cyclophosphamide pulse therapy. Renal biopsy was performed two years after disease onset; light microscopy showed glomerular segmental mesangio-proliferative lesions, and type IV collagen staining showed the loss of the α3 chain in the glomerular and tubular basement membrane (GBM and TBM) and α5 chain loss in the GBM. Electron microscopy showed uneven GBM thickness, with the dense basement membrane (BM) layer obviously delaminated and torn, showing a typical "lace-like" change. The segmental BM was loosened and widened. Her father did not develop microscopic hematuria until 10 years later, while her grandmother had asymptomatic hematuria and proteinuria when the proband was diagnosed. We detected a new COL4A4 mutation in the proband, namely c.1715delG (p.G572Vfs * 81) in exon 24. Her father and grandmother carried the same mutation, but her mother and sister did not. Conclusions: We found a new potentially pathogenic mutation of COL4A4 in a patient with autosomal-inherited AS, which presented as nephrotic syndrome in infancy.